Analisis Kemampuan Membaca Memahami Teks Bahasa Jerman - Dewi Yani Sukirman; Hasmawati Hasmawati; Syarifah Fathimah Al-Ilmul (Phonologie : Journal of Language and Literature, 2021)
Abstract. The purpose of this study was to determine the students' ability to read and understand German texts and the factors that influence their ability to read and understand German texts in class XI Social Sciences at SMA Negeri 8 Makassar. This research is descriptive quantitative. Data were obtained through written tests and questionnaires. The data were analyzed using the percentage technique. The population in this study were students of class XI IPS SMA Negeri 8 Makassar which consisted of 3 classes with a total of 105 students. The sample of this research is the students of class XI IPS 2 SMA Negeri 8 Makassar as many as 25 students who were selected by random sampling technique. The results of this study indicate that the ability to read and understand German texts in class XI SMA Negeri 8 Makassar is included in the sufficient category (65%).